Analisis Gangguan Hubung Singkat 3 Fasa Pada Sistem Kelistrikan PT. Petrokimia Gresik Pabrik Utilitas 1A - Wahid Julianto; Denny Irawan (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
PT. Petrokimia Gresik is a company under the auspices of Pupuk Indonesia Persero which has the main task of supplying subsidized and non-subsidized fertilizers to all regions of Indonesia. To maintain the stability of fertilizers in the Indonesian market, a reliable electrical system is needed so as not to disrupt the production process. The electrical power system at the factory is very prone to disturbances, both short 3-phase interruptions, overload and phase to ground. If this interference cannot be minimized, it can cause damage to the installed equipment. To minimize the above conditions, it is necessary to have a security system and adequate security equipment. One of the safeguards used by PT. Petrokimia Gresik is a protection relay located at the 1A Utility factory.In this study, the Etap Power Station version 12.6 software will be used, the application will be very helpful in calculating short circuits that occur on 6 KV Busbars and 400 V Busbars. With the help of this software, we can analyze the ability of the Bus to short circuit disturbances. From the calculation results obtained, it shows that the busbar bracing ability and the capacity of the circuit breaker installed in the electrical system of PT. Is Petrokimia Gresik still good enough to withstand the existing disturbances.